A comprehensive study of a novel multigeneration system using a combined power plant based on geothermal energy and oxyfuel combustion. (1st July 2023) - Liu, Xiaojuan; Zhao, Hanyu; Huang, Zequan; Shi, Shuyang; Guo, Rongnan; Ding, Pan; Xie, Shaobo
Abstract: In order to increase the energy density and generate more products in a sustainable framework, the current study proposes a geothermal-driven power plant combined with an electrolyzer, boosted by an oxyfuel combustion power plant for a novel multigeneration task. The system produces power, heating, methanol, and carbon dioxide (CO2 ) in a coherent manner, benefiting from low-emission framework and high thermodynamic performance. This system has not been evaluated before. The proposed system consists of a combined flash and binary geothermal plant, a hydrogen production unit, an oxyfuel power unit, a heat and power generation unit, a transcritical CO2 Brayton cycle, a steam Rankine cycle, and a methanol generation unit. Hence, the proposed system is analyzed from the energy, exergy, environmental, and economic points of view. In addition, a parametric analysis is performed to assess the effects of some basic thermodynamic parameters on the cycle performance. The parametric study reveals that the increase in the working fluid temperature leads to an increase in the net power and energy and exergy efficiencies, and low pressure of the gas turbine is an important factor for enhancing the total thermodynamic efficiency of the system. Also, the system's energy and exergy efficiencies together with the total unit cost of products are found to be 47.2%, 40.34%, and 5.53 G J, respectively. Moreover, the CO2 footprint corresponding to the electricity and methanol outputs are obtained at 0.0023 k g C O 2 k W h and 0.056 k g C O 2 k g M e O H, respectively.